Dziewiętnastowieczni wydawcy polskich książek dla dzieci i młodzieży - Boczar, Elżbieta (Acta Universitatis Lodziensis. Folia Librorum, 2014)
Literature for children and young people have played a specific role during the years when Poland was partitioned. Polish books were useful to raise the level of young readers’ education, teach the history of their nation and maintain national consciousness. The aim of this article is to present the leading publishing houses of books for children in the Russian occupying zone and determinate the what and how many of these books were made available to juvenile. To find the best way to present the research results, the author fits them into the three periods of children’s literature: the first includes the publishing of books for children before the November Uprising; the second is concentrated on the editing of books addressed to juvenile until the January Uprising (1831-1862); the third is devoted to the growth in the publishing of literature for the young reader at the end of the 19th century.